2017
DOI: 10.1177/1090198117715666
|View full text |Cite
|
Sign up to set email alerts
|

Energy Balance–Related Behavior and Anthropometric Measures Among Adolescents Across Three Educational Levels: A Cross-Sectional Study in Dutch Schools

Abstract: Energy balance-related behavior on schooldays and beliefs about school-based interventions may differ between students in different educational levels, sexes, and BMI (body mass index) categories. In Zwolle (the Netherlands), 1,084 adolescents (13-15 years) at 9 secondary schools completed a questionnaire. Overweight prevalence (boys 18.1%, girls 19.3%) increased with decreasing educational level, especially in boys. Girls reported healthier behavior than boys regarding daily consumption of fruit (35% vs. 29%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
4
2
0
Order By: Relevance
“…Results in comparable studies show a positive impact of knowledge on food consumption and nutritional behaviour in children and adolescents: Intake of foods considered to be healthy, such as vegetables, fruits and starchy foods, was often higher when nutrition knowledge was higher, while consumption of unhealthy foods such as sweets, snacks, fried foods and sugary drinks was negatively associated with nutrition knowledge (7,30) . Similar to our study, studies have also shown a significant difference between boys and girls, demonstrating boys having lower nutrition knowledge and lower consumption of vegetables and fruits but a higher consumption of meats, fats and soft drinks compared with girls (7,65,66) . On the other hand, there are also several studies with no significant associations between nutrition knowledge and dietary behaviour, which confirms again that dietary behaviour and lifestyle are a multifactorial result of various influences of psychological, behavioural, genetic, environmental, socio-economic and sociodemographic origin (32,33) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results in comparable studies show a positive impact of knowledge on food consumption and nutritional behaviour in children and adolescents: Intake of foods considered to be healthy, such as vegetables, fruits and starchy foods, was often higher when nutrition knowledge was higher, while consumption of unhealthy foods such as sweets, snacks, fried foods and sugary drinks was negatively associated with nutrition knowledge (7,30) . Similar to our study, studies have also shown a significant difference between boys and girls, demonstrating boys having lower nutrition knowledge and lower consumption of vegetables and fruits but a higher consumption of meats, fats and soft drinks compared with girls (7,65,66) . On the other hand, there are also several studies with no significant associations between nutrition knowledge and dietary behaviour, which confirms again that dietary behaviour and lifestyle are a multifactorial result of various influences of psychological, behavioural, genetic, environmental, socio-economic and sociodemographic origin (32,33) .…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our findings illustrate a positive association between nutrition education hours per week and healthier food choices, for example, a higher intake of whole grains and a lower intake of meat and energy drinks. Current studies investigating the association of nutrition education as part of the curriculum and dietary behaviour are rare but there are numerous studies showing that nutrition interventions at school, targeting the improvement of the consumption of healthy foodstuffs such as vegetables and fruits in children and adolescents, accompanied by adjustments of the school food environment, can be successful (65,(68)(69)(70)(71)(72)(73)(74) . Nonetheless, a review found that the lack of fidelity in peer-led interventions, lack of behaviour support for environmental interventions and too-short duration (under 5 months) were factors that contributed to the failing of some of the reviewed interventions (75) .…”
Section: Discussionmentioning
confidence: 99%
“…The most popular proposed intervention strategies were offering affordable F&V in the university canteen and university supermarket. Similar results were found in a Dutch study which reported that students aged between 13 and 15 years expected that free fruit at school would stimulate healthy dietary behaviours ( 34 ) . Moreover, Australian university students reported that they would like an increased availability of fresh fruit on the university campus ( 35 ) .…”
Section: Discussionsupporting
confidence: 88%
“…This outcome confirms the notion that supermarkets constitute an important setting for food or drink purchases during school hours. In line with previous studies, most of the adolescents in our sample reported purchasing unhealthy foods or drinks during school hours (He et al, 2012; Ridder et al, 2017). In one study, almost one third of all Dutch adolescents between the ages of 13 and 15 years purchased unhealthy snacks and sugary drinks within the school (19.7% and 11.2%, respectively) or in stores nearby the school (17.9% and 14.4%, respectively) at least 3 days per week (Ridder et al, 2017).…”
Section: Discussionsupporting
confidence: 90%